Una armonía de caprichos : el discurso de respuesta en la prosa de Rubén Darío - Solares Larrave, Francisco José (North Carolina studies in the Romance languages and literatures, 2007)
Through a political and cultural reading of Ruben Dario's canonical works, Francisco Solares-Larrave articulates an innovative view of Spanish American modernismoas a cultural reply to Europe. Unlike other studies of the politics of the movement, which explore Dario's overt political works, this study looks for the covert, less evident political statements in his artistic literary and journalistic prose. Solares-Larrave demonstrates the cultural transformations of the time while presenting Dario's contributions to Spanish American literature as his reply to Europe, the cultural center of the time. The rebelliousness, political awareness, and cultural criticism that appear in Dario's prose make a sharp contrast to his traditional image as a writer blind to the political and social circumstances of the time, whose work was derided as escapist and shallow.